5' Unlocked Nucleic Acid Modification Improves siRNA Targeting - Nicholas M Snead; Julie R Escamilla-Powers; John J Rossi; Anton P McCaffrey (Elsevier, 2013)
Optimization of small interfering RNAs (siRNAs) is important in RNA interference (RNAi)-based therapeutic development. Some specific chemical modifications can control which siRNA strand is selected by the RNA-induced silencing complex (RISC) for gene silencing. Intended strand selection will increase potency and reduce off-target effects from the unintended strand. Sometimes, blocking RISC loading of the unintended strand leads to improved intended strand-silencing potency, but the generality of this phenomenon is unclear. Specifically, unlocked nucleic acid (UNA) modification of the 5' end of canonical (i.e., 19+2) siRNAs abrogates gene silencing of the modified strand, but the fate and potency of the unmodified strand has not been investigated. Here, we show that 5' UNA-modified siRNAs show improved silencing potency of the unmodified strand. We harness this advantageous property in a therapeutic context, where a limited target region in a conserved HIV 5' long terminal repeat U5 region would otherwise yield siRNAs with undesired strand selection properties and poor silencing. Applying 5' UNA modification to the unintended sense (S) strand of these otherwise poorly targeted siRNAs dramatically improves on-target silencing by the intended antisense (AS) strand in pNL4-3.luciferase studies. This study highlights the utility of 5' UNA siRNA modification in therapeutic contexts where siRNA sequence selection is constrained.